Explanation:
According to Newton's law of universal gravitation:
[tex]F=G\frac{Mm}{a^2}[/tex] (1)
Where:
[tex]F[/tex] is the module of the force exerted between both bodies
[tex]G[/tex] is the universal gravitation constant.
[tex]M[/tex] and [tex]m[/tex] are the masses of both bodies.
[tex]a[/tex] is the distance between both bodies
If we apply this law for two bodies in a circular orbit:
[tex]G\frac{Mm}{a^2}=m{\omega}^{2}a[/tex] (2)
Where:
[tex]\omega=\frac{2\pi}{T}[/tex] is the angular velocity, which is related to the period of the orbit [tex]T[/tex]
Substituting [tex]\omega[/tex] in (2):
[tex]G\frac{Mm}{a^2}=m{(\frac{2\pi}{T})}^{2}a[/tex] (3)
Finding [tex]T^{2}[/tex]:
[tex]T^{2}=\frac{4\pi^{2}}{GM}a^{3}[/tex] (4)
Knowing [tex]\frac{4\pi^{2}}{GM}=C[/tex] is a constant:
[tex]T^{2}=Ca^{3}[/tex]
We finally get to 3rd Kepler's law of planetary motion:
[tex]\frac{T^{2}}{a^{3}}=C[/tex] (5)